Static deflection and thermal stress analysis of non-uniformly heated tapered composite laminate plates with ply drop-off. (August 2018) - Ashok, Shushanth; Jeyaraj, Pitchaimani
Abstract: The effective design of tapered laminated composite structures subject to non-uniform temperature fields requires a thorough understanding of their static behaviour. In this study, a finite element analysis of tapered laminated composite plates with ply drop-off has been carried out to study the static deflection and normal stress patterns developed under non-uniform heating. The study revealed that the nature of the taper configuration, the nature of the applied temperature field and the structural boundary conditions influence the static deflection behaviour and the normal stresses developed in the tapered composite plates. It is found that the static deflection pattern of a tapered plate subject to a particular temperature profile is not sensitive to the nature of the taper configuration. It is also observed that the static deflection pattern of a tapered plate is significantly influenced by the nature of temperature field. Normal stress variation of tapered plates subject to various temperature fields reflects the nature of the temperature profile. Maximum normal stress occurs at locations where the highest temperature exists for that particular temperature field. The stresses are also influenced by the nature of the taper - Taper D plates experience low stresses while Taper B and Taper C plates experience similar values. It was also found that large variations in stresses are observed at resin pockets.